Performance Measurement: A Stakeholder Approach - Niki Lukviarman (Sinergi: Kajian Bisnis dan Manajemen, 2008)
It is important that companies maintain their contractual relationships with their stakeholder groups. Therefore, a company’s strategy needs to accommodate these relation-ships and, consequently, there is a need for appropriate performance measurement to deter-mine how well the company serves its stakeholders. Based on a literature review, this paper seeks to observe current performance measurement models from the view of stakeholder theo-ry. Although broader performance measurement models have been introduced in response to the existence of stakeholders, these models still rely on financial indicators as primary measures whilst using operational indicators as complementary measures. However, these measures have recognized the importance of business performance not only to measure cur-rent outcomes, but also to influence future outcomes. Problems in implementing broader measures of performance include identification of relevant variables, relating action and re-sults, and translation of projects and activities into measurable terms.Keywords: stakeholder, performance measurement, maintaining quality